Chile - Rural Infrastructure in Chile : Enhancing Efficiency and Sustainability - World Bank (Washington, DC, 2013)
This report examines the current institutional and financial arrangements for infrastructure service provision in rural areas of Chile, focusing upon the water, sanitation, electricity, communications and transportation sectors, and proposes mechanisms for improvement. The analysis is based upon cross-sectoral dialogues with a variety of government agencies at the national, regional and municipal levels, government information and supplemental reports, and six background studies commissioned by the World Bank specifically for this work. The recommendations emerging from this cross-sectoral analysis are designed to address two broad sets of needs: (a) to improve the efficiency, sustainability and impact of infrastructure services for the rural population that already has received access, and (b) to develop more appropriate strategies for extending service coverage to those still unserved segments of the rural population. Recommendations are provided for each sector as well as on a cross-sectoral basis.